Pentecostalism and development in Kibera informal settlement, Nairobi - Deacon, G (2012)
This article outlines one of the activities organised by an international Evangelical faith-based development organisation (FBDO) working in the Kibera informal settlement, an area that attracts large numbers of development practitioners, including FBDOs and Christian missionaries. Some Pentecostal and Evangelical perceptions of entrepreneurship are outlined, which are then related to current theoretical descriptions of the role of global Pentecostalism in improving livelihoods and well-being. It is suggested that local conditions in Kibera mean that little improvement in terms of livelihoods is possible. Therefore local Pentecostal adherents tend to utilise their faith and church activities in attempts to survive conditions as they are, rather than in seeking to transform them. It is suggested that members of Pentecostal churches in Kibera seek to express, understand and control, but not change, their challenging lifeworlds through their religious ideas and activities. © 2012 Copyright Taylor and Francis Group, LLC.